Emphysematous pyelonephritis: is conservative management effective? Our experience and review of literature - Khandelwal, Atul Kumar (International Surgery Journal, 2020)
Background: Emphysematous pyelonephritis (EPN) is a urologic emergency caused by a life-threatening necrotizing infection of the kidney leading to an accumulation of gas in the renal parenchyma and perirenal tissue. we present the clinical details and outcome of twelve patients of managed at our institute and discuss their management and outcomes. Methods: Twelve consecutive patients with EPN were managed in our institute from July 2014 to July 2018. Data on demographic profile, clinical features, laboratory investigations, imaging studies, outcome of patients and follow up details were recorded. Results: Out of 12 patients with EPN, nine were female and three were male. Ten patients were diabetic (83%). All the diabetic patient had raised blood sugar at the time of admission ureteric stone was present in two nondiabetic patients. All the patients had fever at the time of presentation while localized flank pain was present in 6 (50%) patients. On examination, renal angle tenderness was present in ten patients while abdominal mass found in three patients. Pyuria was found in all patients while leukocytosis found in 10 patients. Two patients had thrombocytopenia while 4 had deranged renal parameters at the time of admission. Urine culture showed Escherichia coli in 8 patients and Klebsiella in two patients. Four patients required percutaneous drainage. Interval nephrectomy was done in one patient due to non-functioning kidney. Conclusions: Majority of patients diagnosed as emphysematous pyelonephritis were managed conservatively due to diagnosed at an early stage. Percutaneous drainage is successfully utilized in patients with more advanced disease.